Accelerating GPCR Drug Discovery With Conformation-Stabilizing VHHs - Laeremans, Toon; Sands, Zara A.; Claes, Pieter; De Blieck, Ann; De Cesco, Stephane; Triest, Sarah; Busch, Andreas; Felix, David; Kumar, Abhinav; Jaakola, Veli-Pekka; Menet, Christel (Frontiers in Molecular Biosciences, 2022)
The human genome encodes 850 G protein coupled receptors (GPCRs) of which half are considered to be potential drug targets. GPCRs transduce an extracellular stimulus into a plethora of vital physiological processes. Consequently, GPCRs are an attractive drug target class. This is underlined by the fact that approximately 40% of marketed drugs modulate GPCRs. Intriguingly 60% of non-olfactory GPCRs have no drugs or candidates in clinical development, highlighting the continued potential of GPCRs as drug targets. The discovery of small molecules targeting these GPCRs by conventional high throughput screening (HTS) campaigns is challenging. Although the definition of success varies per company, the success rate of HTS for GPCRs is low compared to other target families (Fujioka and Omori, 2012; Dragovitch et al. 2022). Beyond this, GPCR structure determination can be difficult, which oftentimes precludes the application of structure-based drug design approaches to arising HTS hits. GPCR structural studies entail the resource-demanding purification of native receptors, which can be challenging as they are inherently unstable when extracted from the lipid matrix. Also, GPCRs are flexible molecules, adopting distinct conformations some of which need to be stabilized if they are to be structurally resolved. The complexity of targeting distinct therapeutically-relevant GPCR conformations during the early discovery stages contributes to the high attrition rates for GPCR drug discovery programs. Multiple strategies have been explored in attempts to stabilize GPCRs in distinct conformations to better understand their pharmacology. This review will focus on the use of camelid-derived immunoglobulin single variable domains (VHHs) that stabilize disease-relevant pharmacological states (termed ConfoBodies by the authors) of GPCRs, as well as GPCR:signal transducer complexes, to accelerate drug discovery. These VHHs are powerful tools for supporting in vitro screening, for deconvolution of complex GPCR pharmacology, and for structural biology purposes. To demonstrate the potential impact of ConfoBodies on translational research, examples are presented of their role in active-state screening campaigns and structure-informed rational design for the purpose of identifying de novo chemical space, and subsequently, how such matter can be elaborated into more potent and selective drug candidates with intended pharmacology.